The analysis of the effect of printing orientation parameter on the surface roughness of 3D metal printed specimens - Abu Zaki, Muhammad Syafiq Syazwan; Taib, Mohd Taufik; Abu Bakar, Mohd Hadzley (Universiti Malaysia Perlis, 2024)
Designing and manufacturing work related to the utilization of rapid prototyping and 3D CAD modeling is popular nowadays since this method is convenient compared to other traditional design and manufacturing methods. The investigation of the effect of 3D printing parameters on surface roughness is familiar since many types of 3D printing machines have been created at present. But for the Selective Laser Melting (SLM) 3D printing machine, the surface roughness experiments are difficult to execute as the SLM's specimens are using metal as the main material. Besides, there are limited studies of previous researchers that study the surface roughness of SLM specimens. Therefore, this paper will discuss the study of the effect of SLM 3D printing parameters on surface roughness using metal (Stainless steel) as the main material. The printing parameters were: the effect of surface area, the effect of height, and the effect of angle printing. Each parameter consists of 3 specimens with different dimensions and orientations. The result will determine which printing condition will give the best result of surface roughness.